2004
DOI: 10.3928/0147-7447-20040102-17
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Bone Morphogenetic Proteins and Other Growth Factors in Demineralized Bone Matrix

Abstract: Osteoinductive of demineralized bone matrix has been attributed to bone morphogenetic proteins (BMP). Other growth factors, including insulin-like growth factor-l (ICF-I) and transforming growth factor-ß1 (TGFßl), have also been detected in demineralized bone matrix. Success of bone graft substitutes containing demineralized bone matrix has been assumed to be closely associated with osteoinductivity of the demineralized bone matrix. Because of differences in bone characteristics between donors and tissue banks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 17 publications
1
36
1
4
Order By: Relevance
“…As an important aspect of a tissue engineered scaffold is to promote cellular attachment and cell recruitment,24, 33 increasing the attachment of hFOB is an encouraging step towards using the HAp‐PEI‐BMP‐2 for bone regeneration. Several studies have also shown that BMP‐2 attached to the scaffold surface have osteogenic effects at BMP‐2 levels closely resembling physiological levels 34–36. Karageorgiou et al17 covalently bonded BMP‐2 to silk fibroin at a concentration of ∼30 ng/cm 2 and showed an increase in ALP activity in vitro after 2 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…As an important aspect of a tissue engineered scaffold is to promote cellular attachment and cell recruitment,24, 33 increasing the attachment of hFOB is an encouraging step towards using the HAp‐PEI‐BMP‐2 for bone regeneration. Several studies have also shown that BMP‐2 attached to the scaffold surface have osteogenic effects at BMP‐2 levels closely resembling physiological levels 34–36. Karageorgiou et al17 covalently bonded BMP‐2 to silk fibroin at a concentration of ∼30 ng/cm 2 and showed an increase in ALP activity in vitro after 2 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…Aside from BMPs in DBM, there may be additional endogenous growth factor considerations. The quantity of insulin-like growth factor I (IGF-I) and transforming growth factor beta (TGF-in DBM may have co-regulatory affects on BMP [85]. It is noteworthy that IGF-I and TGF-remain relatively consistent during aging [86].…”
Section: Osteoinduction: Donor Gender and Agementioning
confidence: 99%
“…Although BMP-2 was originally isolated as a putative inductive factor in DBP, these results show that rhBMP-2 and DBP do not affect all the Wnt components in the same ways. Because Guanidine HCl/ EDTA extracts of demineralized bone contain BMP-2, BMP-4, BMP-7/OP-1, TGF-b1, IGF-I, and other biologically active proteins, 21,22 we proposed that it was unlikely that a single component could duplicate all of the effects of DBP. 6,10 We reported previously that DBP and BMP-2 regulate common and distinct signaling pathways, that DBP stimulates both Smad pathways, the one responsive to TGF/Activin and the one responsive to BMP, 10 and that DBP evoked early changes in Wnt components.…”
Section: Discussionmentioning
confidence: 99%